A Pursuit of Indonesian SMEs (Small-Medium Enterprises) towards Green SMEs - Erlangga, Okyviandi Putra; Mi’raj, Denizar Abdurrahman (International Journal of Psychosocial Rehabilitation, 2020)
Indonesian Small and Medium Enterprises (SMEs) are the largest business sector and an important component of the nations economic development. However, limited studies are examined in the development of SMEs, challenges and opportunities for green business in the future. Therefore this article discusses the development of SMEs in Indonesia, challenges and environmentally friendly business opportunities among SMEs that play an important role in the nation’s growth. The main point of the studies examined in this paper is that Indonesian SMEs contribute to the largest business establishment in Indonesia and most of them are in micro-size establishments. The uniqueness of this paper focuses on the role of Indonesian SMEs and their contribution and strategies for SMEs that can be done towards green SMEs.